2015
DOI: 10.1097/mib.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Circulating MicroRNAs for the Diagnosis and Disease Activity Evaluation in Patients with Ulcerative Colitis by Using the Nanostring Technology

Abstract: Background: Clinical decision and patient care management in inflammatory bowel diseases is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…The concept of a circulating miRNA signature has been suggested as being more valuable and practical for various diseases, including IBD. Although relatively few studies have quantitatively assessed circulating miRNAs in patients with IBD, some differences in miRNA expression have been observed in sera from patients with either CD or UC 4347 . A recent study has identified a set of 4 miRNAs that correlated with UC disease activity with higher specificity and sensitivity than CRP 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a circulating miRNA signature has been suggested as being more valuable and practical for various diseases, including IBD. Although relatively few studies have quantitatively assessed circulating miRNAs in patients with IBD, some differences in miRNA expression have been observed in sera from patients with either CD or UC 4347 . A recent study has identified a set of 4 miRNAs that correlated with UC disease activity with higher specificity and sensitivity than CRP 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although relatively few studies have quantitatively assessed circulating miRNAs in patients with IBD, some differences in miRNA expression have been observed in sera from patients with either CD or UC 4347 . A recent study has identified a set of 4 miRNAs that correlated with UC disease activity with higher specificity and sensitivity than CRP 47 . The potential use of such panels for distinguishing between CD and UC has been described 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of circulating miR-1827 in serum was also found to be decreased in ulcerative colitis patients, who have an increased risk for colorectal cancer21. Further work indicated a novel role for miR-1827 indirectly targeting mouse double minute 2 (MDM2) to regulate p53, which in turn suppresses colorectal tumorigenesis17.…”
Section: Discussionmentioning
confidence: 98%
“…Patients that were in remission by week 14 of therapy had elevated levels of let-7d and let-7e compared to non-responders [58]. Several recent studies found miR-223 to be elevated in the peripheral blood and serum of CD and UC patients [46,47,49]. Polytarchou and colleagues reported that serum miR-223-3p, miR-4454, miR23a-3p, and miR320e levels correlated with UC disease activity better than serum C-reactive protein levels [46].…”
Section: Circulating Mirna Expressionmentioning
confidence: 99%